Penggunaan Metode Arkeologi Foucauldian untuk Studi-Studi Media - Listiorini, Dina (Jurnal ILMU KOMUNIKASI, 2024)
This article aims to explain one of the Foucauldian discourse methods in studying media phenomena and elaborating communication artifacts or archives, namely archaeology.  The article is based on a literature review that systematically integrates, analyses, and elucidates the presentation of the Foucauldian archaeological method. The archaeological concepts explored include rupture, breaks, discontinuity, threshold, limit, series, mutation, and transformation, all of which highlight the formation of marginal and forgotten discourses (or groups). To achieve this, a multilevel analysis is required at the micro, meso, and macro levels, grounded in concepts and methods that are informed by the historicity of discursive statements.